PENGARUH DESENTRALISASI FISKAL, LUAS WILAYAH, DAN SISA LEBIH PEMBIAYAAN ANGGARAN TERHADAP PENGALOKASIAN BELANJA MODAL (Studi Empiris Pada Kabupaten Dan Kota Di Provinsi Jawa Timur) - Cahyani Nurlaela; Nur Hidayati; Abdul Wahid Mahsuni (Universitas Islam Malang, 2018)
ABSTRACTThis study aims to examine and find the effect of Fiscal Decentralization,Area Size, and More Budget Financing on the Allocation of Capital Expenditures.The population in this study is the District and City Budget Realization Reportthroughout East Java Province in 2014-2016. The sample used is the entirepopulation used as a sample. The analysis used is multiple linear regression and ttest to see the Effect of Fiscal Decentralization, Area Size, and More BudgetFinancing Remaining on the Allocation of Capital Expenditures.The test results show that: 1) Fiscal Decentralization, Area Size, and MoreBudget Financing simultaneously have a significant effect on the Allocation ofCapital Expenditures, 2) Fiscal Decentralization has a significant positive effecton the Allocation of Capital Expenditures, 3) Area Size has a significant positiveeffect on the Allocation of Capital Expenditures , 4) More Budget FinancingRemaining has a significant positive effect on Capital Expenditure Allocation.Keywords: Fiscal Decentralization, Area Size, Remaining Budget Financing,Allocation of Capital Expenditures.